Stomach and gut content of Long Neck Croacker-Pseudotolithus typus (Bleeker,1863) from Lagos Lagoon, Nigera - Awotunde Mathew Olatunji (Annals of Marine Science - Peertechz Publications, 2021)
Pseudotolithus typus has been considered to hold great promise for fish farming in Africa, the fish having a wide geographical spread, a high growth rate, resistance to handling stress and well appreciated in a wide number of African countries. Studying its feeding habit, which is an important aspect of its biology, is a crucial knowledge needed for its mass cultivation by fish farmers and also its implication for its management in the wild. The main objective of the study was to investigate the food items and feeding activities of Pseudotolithus typus in the Lagos lagoon, Nigeria. A total of 93 specimens were collected and transported in ice-packed container to the wet laboratory of the Department of Biological Oceanography, Nigerian Institute for Oceanography and Marine Research (NIOMR) for further examination. These specimens were usually collected during early hour of the morning. Specimens were weighed with Camry model EK5350 of 5kg capacity to the nearest 0.10 g after blotting dry with filter paper Specimens were dissected and the gut were carefully removed with the aid of a forceps after dissection. Stomach and gut contents were examined and the individual food organisms sorted and counting the number of each food item present in the gut and stomach of the species and summing up these numbers to obtain the grand number of all food items in its guts. The number of non-empty guts divided by total number of guts examined, multiply by hundred was used to determine the guts repletion index. Index of fullness was measured as the ratio of food weight to body weight as an index of fullness. The sampling methods were season stratified.Data were subjected to one way analysis of variance (ANOVA) and significant differences accepted at P < 0.05 using statistical package (SPSS version 14). The diet of Pseudotolithus typus was also analyzed. Frequency of occurrence, numerical abundance and Gut repletion index, stomach fullness were computed. The major dietary components of the species were shrimps. The food composition of P. typus shows seasonal variation with Bivalves conspicuously absent during the dry season. The frequency of occurrence of items in order of abundance revealed crustaceans (Peaneus notialis, Parapenaeopsis longirostrics and unidientified digested shrimps) followed undigested partly digested food items and less common items. The diet composition of the Pseudotolithus typhus indicates they are specialised feeders depending on similar food sources with minimum number of dietary prey items. Shrimps and to some extent juvenile fishes constitute the important preys of Pseudotolithus typhus. Therefore the revolution of the abundance of food items must be assessed for their sustainable production and the extent of pollution in Lagos lagoon should be assessed due to the absence of bivalves(during the dry season) which are bio-indictors of pollutant to know what management strategies and control measures are to be taken.